Microwave-assisted synthesis of nicotinonitrile and/or arene-linked bis(chromene-thiazoles) as new VRE and MRSA inhibitors. Issue 24 (17th December 2022) - Mekky, Ahmed E. M.; Sanad, Sherif M. H.
Abstract: Two series of nicotinonitrile and/or arene-linked bis(thiazoles) possessing chromene units are efficiently prepared in this study. A one-pot protocol was designed to prepare the target hybrids involved in the reaction of the respective salicylaldehydes, 2-cyanoethanethioamide, and the appropriate bis(α-haloketone). The reaction was irradiated by microwaves at 100 °C for 40–90 min in dioxane and mediated by piperazine to produce the desired products in 84–95% yields. Nicotinonitrile-linked hybrids 2b, and 2c attached to 6-(4-chlorophenyl) or 6-(4-nitrophenyl) units, respectively, had the best antibacterial activity, particularly against Staphylococcus aureus, and Enterococcus faecalis strains. They showed equipotent efficacy to ciprofloxacin with MIC/MBC values in the ranges from 5.9 to 12.0 µM. Additionally, 2c demonstrated comparable inhibitory activity to linezolid against MRSA and VRE strains with MIC/MBC values ranging from 2.9 to 11.8 µM. The Ames mutagenicity test was used to conclude that 2c was not mutagenic to the Salmonella strains. Graphical Abstract: UF0001